Merger rates of intermediate-mass black hole binaries in nuclear star clusters - Fragione, G; Loeb, A; Kocsis, B; Rasio, FA (American Astronomical Society, 2022)
Repeated mergers of stellar-mass black holes in dense star clusters can produce intermediate-mass black holes (IMBHs). In particular, nuclear star clusters at the centers of galaxies have deep enough potential wells to retain most of the black hole (BH) merger products, in spite of the significant recoil kicks due to anisotropic emission of gravitational radiation. These events can be detected in gravitational waves, which represent an unprecedented opportunity to reveal IMBHs. In this paper, we analyze the statistical results of a wide range of numerical simulations, which encompass different cluster metallicities, initial BH seed masses, and initial BH spins, and we compute the merger rate of IMBH binaries. We find that merger rates are in the range 0.01–10 Gpc−3 yr−1 depending on IMBH masses. We also compute the number of multiband detections in ground-based and space-based observatories. Our model predicts that a few merger events per year should be detectable with LISA, DECIGO, Einstein Telescope (ET), and LIGO for IMBHs with masses ≲1000 M⊙, and a few tens of merger events per year with DECIGO, ET, and LIGO only.